2018
DOI: 10.1177/1455072518766129
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and stress from substance-use disorder among family members in Iceland

Abstract: Aims: This research was designed to explore the extent to which the use of alcohol or drugs by one member of a family affects the psychosocial state of other family members. The study asks whether family members of substance abusers are more likely to report increased depression, anxiety and stress then the general population in Iceland? Are there significant differences between family members; e.g., spouses, parents, adult children and siblings by gender, age, education and income? Data and methods: The instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Those with a poor ability to distinguish between emotions and reasoning have a limited capacity to think critically. This can therefore lead to their emotional reactions and decisions being governed by stress responses [6,19,20]. Furthermore, this data supports the quantitative study carried out to evaluate the levels of satisfaction reported by adult children of dependent substance users in their couple relationships and roles as parents.…”
Section: Adult Children Of Substance Userssupporting
confidence: 74%
See 3 more Smart Citations
“…Those with a poor ability to distinguish between emotions and reasoning have a limited capacity to think critically. This can therefore lead to their emotional reactions and decisions being governed by stress responses [6,19,20]. Furthermore, this data supports the quantitative study carried out to evaluate the levels of satisfaction reported by adult children of dependent substance users in their couple relationships and roles as parents.…”
Section: Adult Children Of Substance Userssupporting
confidence: 74%
“…In a marriage or couple relationship individuals' distress can manifest itself in negative emotions such as anxiety or anger, which can result in avoiding difficult situations, such as intimacy and communication in a couple's relationship [4,6,7]. Research carried out in 2014 using the FACES IV self-evaluation scale and the FSS and FCS scales showed similar results.…”
Section: The Influence Of Substance Use Disorder On Psychosocial Wellmentioning
confidence: 95%
See 2 more Smart Citations
“…In relation to other indicators the ambiance of a family has shown to have the most weight and impact on an individual’s depression, anxiety and stress levels. These are all circumstances that are highlighted in a contribution by Olafsdottir (2018) from Iceland in this issue of NAD . The study contributes to our understanding of the mental wellbeing of family members living with SUD (substance-use disorders).…”
mentioning
confidence: 84%